ENGLISH TEACHERS MOTIVATION AND CHALLENGES IN VOCATIONAL HIGH SCHOOL IN YOGYAKARTA - Indraswari, Veronica Noviatri; Kuswandono, Paulus (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2018)
This study examines English teachers voices regarding the teacher professional development (TPD) experiences in state vocational high school in Yogyakarta, Indonesia. The voices include their motivation and perceived challenges of professional development efforts. The study is a qualitative research employing questionnaire and interviews to gather the data from ten English teachers in state vocational high school. The findings unravel some intrinsic motivations of English teachers and the challenges and needs perceived in doing TPD related to their time management, namely problems related to teaching schedule and time to look after the family. Most teachers also need more training to practice their ICT skills and performance. The suggestions for further studies are also discussed.